Information Society’s Firmware: in the Search after the New Wineskins - Šaulauskas, Marius P. (Problemos, 2003)
The article deals with the critical analysis of the information society’s existential presupposition, or, to use Alistair Duff’s terminology, information society thesis, which to a considerable degree is supposed to lay down a legitimate foundation for the whole field of emerging information society studies. The article argues that even a permanent failure to prove this existential presupposition in whatever weak or strong version cannot deprive the information society studies of the legitimacy. A failure to provide sufficient empirical evidence for the existence of information society depends not so much on the inherent polisemy of employed sociometric criteria, as on the deficiency of the concept of information society itself insofar as it is articulated along the lines of any sociometric approach. Furthermore, an adequate criterion of information society cannot be quantitative, it should be qualitative and formulated counterfactually, i.e. arguing that systematic dysfunction of telematic infrastructure, posited as a conditio sine qua non of habitat, would necessarily undermine the whole societal framework and force it to collapse. Therefore, due to the ex definitio controversial nature of any qualitative conceptualization, the existential presupposition of information society will presere its pivotal status in the future discourse of information society studies.